The Moral Difference between Faces & FaceTime - Karches, Kyle E. (The Hastings Center report, 2023)
Although the technology for telemedicine existed before the Covid-19 pandemic, the need to provide medical services while minimizing the risk of contagion has encouraged its more widespread use. I argue that, although telemedicine can be useful in certain situations, physicians should not consider it an adequate substitute for the office visit. I first provide a narrative account of the experience of telemedicine. I then draw on philosophical critiques of technology to examine how telemedicine has epistemic and ethical effects that make some of the goods of medicine unavailable. Telemedicine rules out an embodied encounter between physician and patient, in which the sense of touch has special importance. The individualized attention facilitated by the in-person visit may better sustain a caring physician-patient relationship. Physicians should criticize attempts by administrators, insurers, or other parties to incentivize the wholesale replacement of traditional office visits with telemedicine.